Point Shaving: Corruption in NCAA Basketball - Wolfers, Justin (American Economic Review, 2006)
A new field of “forensic economics” has begun to emerge, applying price-theoretic models to uncover evidence of corruption in domains previously outside the purview of economists. By emphasizing the incentives that yield corruption, these approaches also provide insight into how to reduce such behavior. This paper contributes to this agenda, highlighting how the structure of gambling on college basketball yields pay-offs to gamblers and players that are both asymmetric and nonlinear, thereby encouraging mutually beneficial effort manipulation through “point shaving.” Initial evidence suggests that point shaving may be quite widespread. The incentives for gambling-related corruption derive from the structure of basketball betting. To highlight a simple example, the University of Pennsylvania played Harvard on March 5, 2005, and was widely expected to win. Rather than offering short odds on Penn winning the game, bookmakers offered an almost even bet (bet $11 to win $10) on whether Penn would win relative to a “spread.” In this example, the spread was 14.5, meaning that a bet on Penn would win only if Penn won the game by 15 or more points, while a bet on Harvard would be successful if Harvard either won, or lost by 14 or fewer points. The incentive for corruption derives directly from the asymmetric incentives of players, who care about winning the game, and gamblers, who care about whether a team beats (or covers) the spread. Indeed, the example above is ripe for corruption: the outcome that maximizes the joint surplus of the Penn players and the gambler occurs when Penn wins the game, but fails to cover the spread (and the gambler has bet on Harvard). The contract required to induce this outcome simply involves the gambler offering a contingent payment to the player, with the contingency being that he pays only if Penn fails to cover the spread. Given the player’s (approximate) indifference over the size of the winning margin, even small bribes may dominate his desire to increase the winning margin above 14 points, and this, in turn, yields large profits for the gambler who has bet accordingly. The betting market offers a simple technology for the gambler to commit to paying this outcomecontingent bribe: he can simply give the player the ticket from a $1,000 bet on his opponent not covering the spread. Such attempts to shave the winning margin below the point spread are colloquially referred to as “point shaving” and form the focus of my inquiry. I start by outlining the type of corruption that theory suggests will be most prevalent: